2020
DOI: 10.1021/acsami.0c17165
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of an AIE-Active Metal–Organic Framework for Sensitive Detection of Explosives in Liquid and Solid Phases

Abstract: Nowadays, the practical applications of metal− organic framework (MOF)-based fluorescence detectors are severely hindered because of the complex synthesis process of linkers or heavy metal contamination. The development of a simple, inexpensive, and environmentally friendly fluorescence sensing system remains a huge challenge. In this study, we designed and synthesized a TPE@γ-CD-MOF-K complex using the facile in situ encapsulation method. The unique pore structure of γ-CD-MOF allowed it to effectively include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…One of such sensors is based on a g-CD-MOF with tetraphenylethylene (TPE) molecules incorporated in its framework. 143 Notably, TPE@K-g-CD-MOF exhibited enhanced fluorescence compared to TPE alone. Furthermore, in the presence of nitro-aromatic compounds, TPE@K-g-CD-MOF showed quenching of its fluorescence intensity endowing it with sensing properties.…”
Section: Sensing and Detectionmentioning
confidence: 98%
See 3 more Smart Citations
“…One of such sensors is based on a g-CD-MOF with tetraphenylethylene (TPE) molecules incorporated in its framework. 143 Notably, TPE@K-g-CD-MOF exhibited enhanced fluorescence compared to TPE alone. Furthermore, in the presence of nitro-aromatic compounds, TPE@K-g-CD-MOF showed quenching of its fluorescence intensity endowing it with sensing properties.…”
Section: Sensing and Detectionmentioning
confidence: 98%
“…These hybrids not only have improved properties over native CD-MOFs but also extend their applications to various fields like sensing and detection, catalysis, separation and removal sciences, anticancer therapy, or more potent drug delivery systems. 72,76,96,136,[139][140][141][142][143][144][145][146][147][148] It has also been noted in some cases that the formation of CD-MOFs hybrids significantly improves the moisture stability of pristine CD-MOFs. 135,136,149,150 3.2.1 Synthesis of CD-MOF hybrids.…”
Section: Cd-mof Hybridsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, metal–organic frameworks (MOFs) as a class of porous crystalline materials with the advantages of adjustable structure, functionalized nature, and high crystallinity have been applied as the detection of target analytes, and it is helpful to further analyze and understand the mechanism of their detecting behavior. As is known, the fluorescence quenching or enhancement of MOFs is mainly attributed to the host–guest interaction. , To date, a number of MOFs for TNP, Fe 3+ , and Cr 2 O 7 2– detection have been reported; for example, Liu et al reported a luminescent Zn-LMOF (JLU-MOF71) which showed highly selective detection of TNP and Fe 3+ . Zang et al reported a 3D MOF (Tb-DSOA) for Fe 3+ detection via luminescence quenching, and the excellent detection performance of Tb-DSOA was attributed to the existence of the noncoordinated sulfonate oxygen atoms in the channels of Tb-DSOA .…”
Section: Introductionmentioning
confidence: 99%